PELAKSANAAN PENGEMBANGAN KARIR GURU DI SMK TI LABBAIKA SAMARINDA - jurnalpps pps; Woro Utari; Kurniawan Kurniawan (Jurnal Manajerial Bisnis, 2021)
This study uses a qualitative descriptive approach because the symptoms of information or information from the observations during the research process indicate that this research occurs naturally and without any manipulation of existing circumstances and conditions. The focus and dimensions of research in this study are to describe the career development of SMK TI Labbaika Samarinda teachers, how the descriptions of SMK TI Labbaika Samarinda teachers, how the planning and constraints faced in the career development of IT Labbaika Samarinda Vocational School teachers. The results of the research after conducting interviews, observation and in-depth analysis.From the interview data presented with the informants, it shows that the planning and implementation of career development has been done in accordance with the guidance and career development of SMK TI Labbaika teachers, which are in accordance with the requirements of career planning, namely planning. it must suit organizational, individual and managerial.